[ 18 F]Fluoroethylflumazenil: a novel tracer for PET imaging of human benzodiazepine receptors - Gründer, Gerhard; Siessmeier, Thomas; Lange-Asschenfeldt, Christian; Vernaleken, Ingo; Buchholz, Hans-Georg; Stoeter, Peter; Drzezga, Alexander; Lüddens, Hartmut; Rösch, Frank; Bartenstein, Peter (European journal of nuclear medicine, 2001)
5-(2'-[18F]Fluoroethyl)flumazenil ([18F]FEF) is a fluorine-18 labelled positron emission tomography (PET) tracer for central benzodiazepine receptors. Compared with the established [11C]flumazenil, it has the advantage of the longer half-life of the fluorine-18 label. After optimisation of its synthesis and determination of its in vitro receptor affinities, we performed first PET studies in humans. PET studies in seven healthy human volunteers were performed on a Siemens ECAT EXACT whole-body scanner after injection of 100-280 MBq [L8F]FEF. In two subjects, a second PET scan was conducted after pretreatment with unlabelled flumazenil (1 mg or 2.5 mg i.v., 3 min before tracer injection). A third subject was studied both with [18F]FEF and with [11C]flumazenil. Brain radioactivity was measured for 60-90 min p.i. and analysed with a region of interest-oriented approach and on a voxelwise basis with spectral analysis. Plasma radioactivity was determined from arterial blood samples and metabolites were determined by high-performance liquid chromatography. In human brain, maximum radioactivity accumulation was observed 4 +/- 2 min p.i., with a fast clearance kinetics resulting in 50% and 20% of maximal activities at about 10 and 30 min, respectively. [18F]FEF uptake followed the known central benzodiazepine receptor distribution in the human brain (occipital cortex >temporal cortex >cerebellum >thalamus >pons). Pretreatment with unlabelled flumazenil resulted in reduced tracer uptake in all brain areas except for receptor-free reference regions like the pons. Parametric images of distribution volume and binding potential generated on a voxelwise basis revealed two- to three-fold lower in vivo receptor binding of [18F]FEF compared with [11C]flumazenil, while relative uptake of [18F]FEF was higher in the cerebellum, most likely owing to its relatively higher affinity for benzodiazepine receptors containing the alpha6 subunit. Metabolism of [18F]FEF was very rapid. Polar metabolites represented about 50%-60% of total plasma radioactivity at 5 min and 80%-90% at 20 min p.i. Although [11C]flumazenil has some advantages over [18F]FEF (higher affinity, slower metabolism, slower kinetics), our results indicate that [18F]FEF is a suitable PET ligand for quantitative assessment of central benzodiazepine receptors, which can be used independently of an on-site cyclotron.